Molecular sex identification of burnt teeth samples based on nested pcr amplification of amelogen1n (amel) and sex-determining region y (sry) gene regions - Yong, Jonathan Lim Jun (Universiti Sains Malaysia, 2016)
Sex determination one of the basic components in victim identification. There are many available methods such as forensic anthropology and conventional DNA typing methods. In this study, nested PCR technique was employed in sex typing of burnt teeth through amelogenin (AMEL) and sex-determining region Y (SRY) sex markers. All 17 teeth samples were burnt at temperatures ranging from 100 °C to 500 °C at 2 - 10 minutes. The whole tooth was used for DNA extraction by phenol-chloroform method. Accurate sex determination was achieved in 13 samples by both AMEL and SRY markers. The SRY marker achieved higher sensitivity compared to AMEL marker. The sensitivity of both markers were improved upon nested PCR. Factors such as degraded DNA materials and the presence of tooth caries greatly affects sex typing results. Insufficient DNA can produce inconclusive results during gel electrophoresis even after PCR amplification. False positive results by SRY marker can be caused by exogenous DNA contamination. Nested PCR proved to be a good method to amplify highly degraded DNA material as it greatly increases the DNA copy, making sex typing possible. Teeth remain as a good source to obtain DNA even the samples are badly damaged or burnt.